Riding High : Horses, Humans and History in South Africa - Swart, Sandra (Book collections on Project MUSE., 2010)
Horses were key to the colonial economies of southern Africa, buttressing the socio-political order and inspiring contemporary imaginations. Just as they had done in Europe, Asia, the Americas and North Africa, these equine colonizers not only provided power and transportation to settlers (and later indigenous peoples) but also helped transform their new biophysical and social environments. The horses introduced to the southern tip of Africa were not only agents but subjects of enduring changes. This book explores the introduction of these horses under VOC rule in the mid-seventeenth century, t.